Flexed radiographic angles for determination of atlantoaxial instability in dogs - White, Dana Ann (Kansas State University, 2019)
Atlantoaxial instability (AAI) is primarily a congenital neurologic disorder of young, toy breed dogs. AAI which was first reported in 1967, is now included in a subset of craniocervical malformations recognized in young small and toy breed dogs as craniocervical junction abnormalities. With AAI, instability can be secondary to bony malformations between the first two cervical vertebrae or ligamentous instability, resulting in spinal cord compression that manifests in varying degrees of neurologic dysfunction and pain. Atlantoaxial instability is also recognized as a congenital condition in people, and objective measures have been proposed in the diagnosis of AAI in humans. The atlantodental interval, used in humans for diagnosis of AAI, is not applicable for veterinary patients, due to the large number of dens abnormalities identified in dogs with AAI. Throughout the years there have been a number of studies trying to improve our ability to diagnosis atlantoaxial instability safely and reliably in dogs; however, there remains no standard protocol for diagnosis based on flexed lateral radiographs. Without the aid of advanced imaging, the diagnosis of AAI in veterinary medicine is largely subjective, based on interpretation of lateral cervical radiographs with a non-standardized degree of flexion. A retrospective case series of dogs diagnosed with AAI was reviewed and compared with prospective case controls to investigate an objective method of diagnosis based on flexed lateral cervical radiographs. Medical records of dogs diagnosed with AAI from three veterinary teaching institutions were reviewed. Flexed lateral cervical radiographs were evaluated to obtain specific measurements based on anatomic landmarks. Means of these measurements were used to determine the position at which normal toy breed dogs (prospective case controls) were radiographed. Flexed lateral radiographs of thirty-one affected cases were positioned at a mean of 51° flexion. When flexed lateral radiographs were evaluated, 90.3% of affected cases could be diagnosed based on evaluation of an atlas to axis angle (AAA) >10°. When Yorkshire terriers, Chihuahuas, and associated mixed populations were evaluated, 22/24 of the affected dogs met a cutoff value for AAA >10°. Flexed lateral radiographs in the control population were positioned at 51 + 10°, and only two of the control dogs were within the AAA cutoff value. There was no difference between the measurements obtained for the flexed lateral radiographs when compared to the exaggerated flexed lateral views in the control population. These findings support the use of mild cervical flexion during positioning to obtain objective measurements for a radiographic diagnosis of AAI in toy breed dogs.
Keywords: Dog; Radiograph; Atlantoxial instability; Flexed